2021
DOI: 10.3389/fpsyg.2021.574115
|View full text |Cite|
|
Sign up to set email alerts
|

The Susceptibility to Persuasion Strategies Among Arab Muslims: The Role of Culture and Acculturation

Abstract: This study is set forth to explore whether the susceptibility to persuasion—as articulated by Cialdini’s persuasion strategies—could vary with culture and acculturation. We examined individuals from the Arabic culture and their susceptibility to persuasion, according to the following strategies: reciprocity, commitment, liking, scarcity, consensus, and authority. The study involved 1,315 Arab Muslims between 18 and 60 years old (Mean = 34.65, SD = 9.16). The respondents were recruited from among residents of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Collectivist cultures emphasize family values such as family cohesion, mutual assistance, and close relations with extended family members 74 . However, Arab cultures are distinguished from East-Asian collectivistic cultures in multiple aspects, including geography, language, family structure 75 , expression of values 76 , and attitude toward authority 77 – 79 . Unjustified generalization of cultures diminishes distinguished cultural features 80 .…”
Section: Introductionmentioning
confidence: 99%
“…Collectivist cultures emphasize family values such as family cohesion, mutual assistance, and close relations with extended family members 74 . However, Arab cultures are distinguished from East-Asian collectivistic cultures in multiple aspects, including geography, language, family structure 75 , expression of values 76 , and attitude toward authority 77 – 79 . Unjustified generalization of cultures diminishes distinguished cultural features 80 .…”
Section: Introductionmentioning
confidence: 99%
“…related appeal to processes of persuasion (Cialdini, et al, 1999;Tormala & Petty, 2002;Watkins, 2001, as cited in Aarons, 2004. Previous studies showed that there are differences between collectivist and individualist cultures with respect to persuasion processes (Alnunu, et al, 2021;Aksit, 2020;Cialdini et al, 1999;Orji, 2016). Therefore, differences in appeal may reflect these cultural influences.…”
Section: Discussionmentioning
confidence: 99%